Preparation and Response to the 2014 Ebola Virus Disease Epidemic in Nigeria—The Experience of a Tertiary Hospital in Nigeria - Ogoina, Dimie (PLoS One, 2016)
INTRODUCTION: The 2014 Ebola Virus Disease (EVD) outbreak elicited global attention and challenged health systems around the world, Nigeria inclusive. We hereby report the preparation and response to the outbreak by a tertiary teaching hospital in Bayelsa State, Nigeria. METHOD: Between 4th August and 31st October 2014, we conducted a mixed cross sectional and qualitative study to ascertain the EVD-related fear, myths and misconceptions among healthcare workers (HCWs), and to evaluate the plans, activities and challenges faced by the hospital during the outbreak. Data was collected using a self-administered questionnaire as well as by documented observations during the outbreak. HCWs were asked to rate their fear of EVD from 1 (no fear) to 10 (highest fear). RESULTS: Out of 189 respondents, majority (>75%) reported uncertainty about the myth that EVD can be prevented by drinking salt water or eating Garcinia kola, while 82% of respondents believed that EVD can be prevented by avoiding crowded places. About 40% of respondents expressed fear ratings of EVD of ≥ 7 out of 10. In response to the outbreak, the hospital established an EVD response team, organised EVD-sensitization and training programmes and commenced routine EVD surveillance activities. An EVD-isolation ward was constructed from an existing ward, a field incinerator was designed, hand sanitizers were produced locally and personal protective equipment were procured. No case of EVD was reported in the hospital, although three false alarms caused panic. Some HCWs adopted overly protective and avoidance behaviours, but these behaviours were abandoned after the outbreak was declared over. CONCLUSION: Our results suggest that the fear, myth and misconceptions were common among HCW during the outbreak. The EVD outbreak, however, helped to strengthen gaps in infection control and emergency preparedness in the hospital. Strategies to allay fear are required to contain future outbreaks of EVD in Nigeria hospitals.